Mapping Patterns and Free Flow Tidal and Bathymetry of Muda Island in Estuary of Kampar River Teluk Meranti Subdistrict of Pelalawan District - Baruza Arrizqa; Mubarak Mubarak; Elizal Elizal (Program Pascasarjana Universitas Riau, 2017)
This study aims to provide an overview map of the pattern and speed of the tide to the ebb and flow towards the tide and bathymetric of Muda Island in estuary of Kampar River, Teluk Meranti Subdistrict of Pelalawan District. This research was conducted in September 2016 held in Muda Island in estuary of Kampar River, Teluk Meranti Subdistrict of Pelalawan District. The method used in this study is a survey method. Tidal current velocity ranges from 0.16 to 0.54 m/sec. The current direction moving toward the southwest parallel to the river flow. Flow velocity ranges recede from 0.15 to 1.09 m/sec. Moving current direction leads to northeast parallel to the river flow. Bathymetric map of Muda Island estuary of Kampar River found the same relative depth between 0.5 to 2 m on the left and right streams and others around the Muda Island and Ketam Island. Type of tidal Muda Island is a mixed - mainly semidiurnal with the value Formzahl (F) = 0.27. The current direction of Muda Island to follow the type of its tidal namely a change in the flow of 2 times, 2 times in the direction of the tide and 2 times towards low tide.